Requisitos específicos de un sistema integrado QHSE (normas ISO 9001: 2015, ISO 14001:2015 y ISO /DIS 45001) con base en la estructura de alto nivel y recomendaciones metodológicas para su implementación. (2017)
The present research has as general objective the design of specific requirements of an integrated QHSE system under the norms ISO 9001: 2015, ISO 14001: 2015 and ISO / DIS 45001 based on the high level structure (HLS) and recommendations for its implementation , For which it was proposed the achievement of three specific objectives oriented to the comparison, integration and implementation of its requirements, evidencing in turn the step by step of a method towards the integration and implementation of management systems under the same structure, Which positively affects the needs of organizations and academia in this context, as well as the deepening and analysis of the requirements proposed by the future ISO 45001 standard against OHSAS 18001: 2007 and its compatibility with ISO standards 9001: 2015 and ISO 14001: 2015.